Ociation of Age, Marital Status and Other Factors with The Perception of Quality of Life (QOL) Among Young Females in Karachi - Asar, Farzana; Hakeem, Rubina (Nurture, 2013)
Karachi is a modern and multicultural city of Pakistan that also faces a variety of problems including frequent suicides due to family problems. Assessment of satisfaction with quality of life of people is important to understand and improve the situation. This small study is an attempt to explore one aspect of this very gigantic issue and has tried to identify factors associated with the perceptions of a selected group of young females with their quality of life. Higher Age, married status and perceived need for money were associated lower perception of quality of life.